Study on the Work Organization at Dairy Farms - Vántus, András (Acta Agraria Debreceniensis, 2020)
Joining the European Union Hungarian producers have advantages but they need to solve some problems too. Only those producers can compete who will be able to produce extra quality milk. However the circumstances of milk production are not up to the task. The author examined the work organization of 7 dairy farms in Hajdú-Bihar County. Data were collected about the situation of farms, equipment of barns, objets of production, work force, qualification of workers, and productivity of work. He examined the applied motivation methods at farms. He concluded that as the number of cows per farm increases work productivity increases too. From the examination it appeared that family farms applied different motivation system from bigger producer organizations. The author put forward proposals for motivation possibilities to improve milk quality, atmosphere, and general feeling of workers.